2016
DOI: 10.1063/1.4943167
|View full text |Cite
|
Sign up to set email alerts
|

Room temperature strong light-matter coupling in three dimensional terahertz meta-atoms

Abstract: We demonstrate strong light-matter coupling in three dimensional terahertz meta-atoms at room temperature. The intersubband transition of semiconductor quantum wells with a parabolic energy potential is strongly coupled to the confined circuital mode of three-dimensional split-ring metal-semiconductor-metal resonators that have an extreme sub-wavelength volume (λ/10). The frequency of these lumped-element resonators is controlled by the size and shape of the external antenna, while the interaction volume remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…They rely on extremely sub-wavelength single units called meta-atoms, whose archetypical example is the split-ring resonator: a sub-wavelength LC circuit where the microscopic capacitor can, in principle, host a semiconductor active region. Passive devices (absorbers, polaritonic structures, 3D metamaterials) based on this concept have been demonstrated [23][24][25]. However, an electrically-injected optoelectronic 'meta-atom' device (a laser or a detector) has yet to be demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…They rely on extremely sub-wavelength single units called meta-atoms, whose archetypical example is the split-ring resonator: a sub-wavelength LC circuit where the microscopic capacitor can, in principle, host a semiconductor active region. Passive devices (absorbers, polaritonic structures, 3D metamaterials) based on this concept have been demonstrated [23][24][25]. However, an electrically-injected optoelectronic 'meta-atom' device (a laser or a detector) has yet to be demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…We can see that the intersubband plasmon frequencies obtained in the two cases strongly differ from our measurement, confirming the analysis presented above. 29,31,32 In order to improve further the strength of the light-matter coupling, we designed a second sample with an identical absorbing region, but with an increased thickness of the cavity (320 nm) and and increased doping density in the outermost GaAs layers (6 × 10 18 cm −3 ). After processing into patch cavities and LC metamaterials, we perform the same experiments as described above (see Supplementary materials for details).…”
mentioning
confidence: 99%
“…Many subsequent studies have demonstrated strong coupling in a variety of systems. Semiconductor microcavity structures containing active inorganic material layers are most frequently reported due to their mixed mode nature and manipulated polariton features, such as GaN high optical quality film in an all‐dielectric cavity, CdTe photonic crystal structure with a series of embedded quantum wells (QWs), and 2D atomic crystal MoS 2 or MoSe 2 embedded in the double microcavity structures . Strong coupling interactions between hyperbolic metamaterial high‐k modes and embedded QW intersubband transitions have also been reported .…”
Section: Introductionmentioning
confidence: 99%